Differentiation and virus expression in BALB/Mo mice: endogenous Moloney leukemia virus is not activated in hematopoietic cells. - Fiedler, W (1982)
The endogenous Moloney leukemia virus (M-MuLV) in the BALB/Mo substrain of mice is activated during the first week after birth. Virus replication occurs in cells of the lymphatic system. Lymphoid cells therefore represent the target cells for virus replication and leukemic transformation. To investigate whether virus activation occurs during lymphoid cell differentiation, hematopoietic stem cells carrying the endogenous Mov-1 genome were transplanted to sublethally irradiated BALB/c mice. Effective colonization of the recipients was demonstrated by Southern DNA hybridization. No activation of the endogenous Mov-1 genome occurred during a 4-month observation period after the transplantation. Thus the first step in development of disease in BALB/Mo mice involves activation of the Mov-1 locus in a nonhematopoietic cell followed by superinfection of lymphatic cells and subsequent virus replication and virus spread.